Pelatihan Online Basic Life Support Tahun 2023 - Siwi, Ignasia Nila (LPPM STIKES Madani, 2024)
Cardiac arrest events are often found by ordinary people. The ability of lay people as first aiders is an important key to the success of saving victims of cardiac arrest. The high mortality rate is the reason why online basic life support (BLS) training is needed. This training aims to improve participants' knowledge and skills related to basic life support. The training method used is practice while watching simulation through online video with three materials namely CPR for adult, CPR for baby and Choking & recovery position skill stations which will be evaluated by each participant. The results of the training found that the knowledge and skills of participants after receiving training and simulation assistance when performing all skills in this activity were better than before being given training.